Pruning management of mini-stumps for mass propagation of blueberry - Stuepp, Carlos André; Amaral, Bruna Aparecida do; Ayub, Ricardo Antonio; Fragoso, Rosimeri de Oliveira (Pesquisa Agropecuaria Brasileira, 2022)
The objective of this work was to evaluate the influence of the pruning management of mini-stumps of the Climax blueberry cultivar, when weekly fertigated, on the productivity of the clonal mini-garden and on the rooting and root vigor of the mini-cuttings. The high survival of the mini-stumps (100%) and production of the mini-cuttings (182.9 mini-cuttings per square meter per month) evidence the high adaptability of the material to successive samplings and to the nutritional conditions provided to the clonal mini-garden, resulting in a high multiplication rate. The rooting percentages obtained at the different samplings remain stable, with a high average of rooted mini-cuttings, reaching 81.7%.